2016
DOI: 10.4172/2472-4998.1000104
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Acute Lobar Nephronia Caused by Enterobacter cloacae

Abstract: Acute lobar nephronia is an uncommon type of urinary tract infection affecting the kidneys and more commonly reported in the pediatrics population. It can be a precursor to renal abscess formation if undertreated. Escherichia coli is the commonest pathogen observed in adults with this condition but other organisms have also been reported. This case report describes a 65-year-old woman whose work-up for fever, nausea and vomiting led to the diagnosis of acute lobar nephronia caused by Enterobacter cloacae. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…There is currently no recommendation on the duration of antibiotics; however the majority of authors suggested a minimum of 4 weeks with repeat imaging in 6 weeks to ensure appropriate resolution and to exclude an underlying renal mass. 1,3,10,11…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no recommendation on the duration of antibiotics; however the majority of authors suggested a minimum of 4 weeks with repeat imaging in 6 weeks to ensure appropriate resolution and to exclude an underlying renal mass. 1,3,10,11…”
Section: Discussionmentioning
confidence: 99%